Pengaruh Video Edukasi Bullying Terhadap Perkembangan Sosial Anak Usia Dini di PAUD Prima Pertiwi - Rizka Fadhilah Daulay; Mira Yanti Lubis; Hopman Daulay (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The aim of this research is to determine: (1) the social development of children in PAUD Prima Pertiwi using bullying educational videos, (2) the influence of bullying educational videos on the social development of early childhood in PAUD Prima Pertiwi, Sayur Mahincat village. This research uses a quantitative approach with an experimental type of research. The research design used a one-group pretest-posttest type pre-experiment. The instruments used consisted of observations, interviews and tests. The data analysis technique uses descriptive statistics and carries out conditional tests, namely the normality test and homogeneity test. Test the hypothesis using the